Analysis of The Utilization of the Social Center for Orangutan Protection (COP) In Kalimantan in Orangutan Saving Efforts: Analisis Pemanfaatan Jaringan Sosial Centre for Orangutan Protection (COP) di Kalimantan Dalam Upaya Penyelamatan Orangutan - Hardiyanti, Octalina; Nurmanina, Agustin (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
ABSTRACT: Utilization of the Center for Orangutan Protection (COP) 2 social network in Kalimantan. With the limited number of human resources compared to the wide scope of work in all of Kalimantan, COP makes use of its social networks to meet the needs and the functioning of the organization. In investigative activities, COP has effectively used weak ties to obtain information on the whereabouts of orangutans and the destruction of their habitat. The policies in this activity are also dominated by central actors through their power networks which result in network stability. In contrast to the use of social networks for educational activities, local actors are more dominant in making program policies and work patterns. In the alternation between actors from time to time, there are differences in assumptions and work patterns of the actors in charge, resulting in differences in utilization results and potential network damage. COP can utilize its social network in fulfilling its function as an NGO campaigning for the protection and rescue of orangutans, but on the other hand, COP's bonding social network only connects this NGO with similar organizations, limited to handling cases of orangutans and their habitat. Supporting nature conservation, such as economic, social, and cultural, as part of the needs of the community around the ring habitat is not fulfilled. ABSTRAK: Pemanfaatan jaringan sosial Centre for Orangutan Protection (COP)2 di Kalimantan. Dengan keterbatasan jumlah SDM dibanding luasnya cakupan kerja di seluruh Kalimantan, COP memanfaatkan jaringan sosialnya untuk memenuhi kebutuhan dan berjalannya fungsi organisasi. Dalam kegiatan investigasi COP efektif menggunakan ikatan lemah untuk memperoleh informasi keberadaan orangutan dan perusakan habitatnya. Kebijakan dalam aktivitas ini pun didominasi aktor pusat melalui jaringan powernya yang menghasilkan stabilitas jaringan. Berbeda dengan pemanfaatan jaringan sosial untuk kegiatan edukasi, aktor lokal lebih dominan mengambil kebijakan program dan pola kerja. Dalam pergantian antar aktor pada masa ke masa terdapat perbedaan asumsi dan pola kerja aktor-aktor yang bertugas sehingga menimbulkan perbedaan hasil pemanfaatan hingga potensi terjadinya kerusakan jaringan. COP mampu memanfaatkan jaringan sosialnya dalam memenuhi fungsinya sebagai LSM yang mengkampanyekan perlindungan dan penyelamatan orangutan, namun sisi lainnya jaringan sosial COP yang bersifat bonding (tertutup) hanya menghubungkan LSM ini dengan organisasi sejenis terbatas pada penanganan kasus orangutan dan habitatnya. Pendukung konservasi alam seperti ekonomi, sosial dan budaya sebagai bagian dari kebutuhan masyarakat di sekitar ring habitat tak terpenuhi.